2020
DOI: 10.3390/app10020478
|View full text |Cite
|
Sign up to set email alerts
|

Self-Mixing Interferometry-Based Micro Flow Cytometry System for Label-Free Cells Classification

Abstract: In this paper, we present a novel optical microfluidic cytometry scheme for label-free detection of cells that is based on the self-mixing interferometry (SMI) technique. This device enables simple, fast and accurate detection of the individual cell characteristics and efficient cell type classification. We also propose a novel parameter to classify the cell or particle size. Artificial polystyrene beads and human living cells were measured using this system, and the SMI signal properties were statistically ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is also worth mentioning the contribution of SMI to flow cytometry (FC) for cell type discrimination and size classification using SMI. Unlike most conventional Flow Cytometry (FC) techniques, the proposed system does not require of a fluorescence labeling pretreatment with expensive dyes that can also damage the cells samples under study [ 88 ]. Despite the existing well-established label-free FC schemes, the requirement of expensive devices, such as high-speed cameras and ultrasound transducers, and the complexity of the existing technology, are shortcomings that an SMI-based flow cytometer is able to overcome.…”
Section: Self-mixing Interferometrymentioning
confidence: 99%
“…It is also worth mentioning the contribution of SMI to flow cytometry (FC) for cell type discrimination and size classification using SMI. Unlike most conventional Flow Cytometry (FC) techniques, the proposed system does not require of a fluorescence labeling pretreatment with expensive dyes that can also damage the cells samples under study [ 88 ]. Despite the existing well-established label-free FC schemes, the requirement of expensive devices, such as high-speed cameras and ultrasound transducers, and the complexity of the existing technology, are shortcomings that an SMI-based flow cytometer is able to overcome.…”
Section: Self-mixing Interferometrymentioning
confidence: 99%
“…2) Obtaining 512 discrete samples by sampling 0 ( ) I t and 1 ( ) I t over a rising or falling part of / 2 T  , as shown by (6) and (7). Applying 512-point FFT on the two discrete sequences 0 ( ) s I nT and 1 ( ) s I nT , as shown by (8) and (12). 3) Using (9) and (13) , where 0 d = 100 nm and t f = 10 Hz.…”
Section: A Simulation Testmentioning
confidence: 99%
“…Various SMI-based sensing applications have been reported, including the measurement of displacement, velocity, vibration, laser related parameters, thickness, mechanical resonance [1][2][3][4][5][6][7], etc. Recently, SMI-based sensing has been extended for imaging, material parameter measurement, near-field microscopy, chaotic radar, acoustic detection, biomedical applications [8][9][10][11][12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported high-throughput IFC by combining a quantitative phase imaging platform with time-stretch optical microscopy for the classification of human leukemic cell types (28). In addition, Zhao et al presented an optical microfluidic cytometry scheme for label-free detection of cells, which is based on self-mixing interferometry technique (29). Merola et al demonstrated that by exploiting the rolling of cells while they flow along a microfluidic channel, it is possible to obtain single-cell interferometric tomography for red blood cells (30).…”
Section: Introductionmentioning
confidence: 99%